Justice of God in Kant’s Philosophy: for a Human Being and a State - Putinaitė, Nerija (Problemos, 1999)
The paper is an inquiry into the concept of retributive justice in Kant’s “Religion within the Bounds of Reason Alone” (1795). Kant proposes an explanation of theological terms (God, grace, punishment, and discharge) in the common field of moral and politic realms. We find two kinds of justice as well as of worlds contrasted in Kant’s philosophy: world of the absolute justice of God, and world of human justice. The strongest, rule-based justice is to be exercised in the world of human beings. This kind of justice must be based on the principles of speculative rationality alone. The justice of God is based on two principles: that of prudence and of grace. The possibility of grace that surpasses the speculative ability of human being is a secret or mystery to him. Grace refers to and forms an inner moral historicity of human being. The source of historicity is change of human natural state of guilt and punishment into the state of joyful inner moral development. Only grace makes it possible for human being to change his moral inclinations from vicious to virtuous. Kant considers pain caused by vicious inclinations as a sign of God’s retributive justice. The paper raises questions about the possibility of discharge. Hypothesis is held that discharge takes place in time. It shows itself as the inner moral development of the human being and the state. The controversial notions of apologists and critics of Kant’s philosophy are presented.